1998
DOI: 10.1084/jem.188.11.2181
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Paradox of CD43 in Leukocyte Recruitment: A Study Using CD43-deficient Mice

Abstract: Although there is considerable evidence implicating a role for CD43 (leukosialin) in leukocyte cell–cell interactions, its precise function remains uncertain. Using CD43-deficient mice (CD43−/−) and intravital microscopy to directly visualize leukocyte interactions in vivo, we investigated the role of CD43 in leukocyte–endothelial cell interactions within the cremasteric microcirculation under flow conditions. Our studies demonstrated significantly enhanced leukocyte rolling and adhesion after chemotactic stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
64
1
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 33 publications
(44 reference statements)
4
64
1
5
Order By: Relevance
“…These data, along with previously published studies, point toward a leukocyte subset-specific repertoire of ligands for E-selectin: whereas PSGL-1 and CD44 appear to contribute to binding activity in both myeloid and T lymphocytes ( 6,10,11 and the present study), the activity of CD43 appears to be restricted to T lymphocytes 5,7,45 and that of ESL-1 likely to neutrophils. 7,11 Moreover, our studies suggest that each of these ligands makes a specialized contribution to the different steps of leukocyte recruitment: both PSGL-1 and CD43 localize to the microvillus projections 46,47 and are therefore more suitable to mediate tethering and initial rolling interactions.…”
Section: Discussionsupporting
confidence: 50%
“…These data, along with previously published studies, point toward a leukocyte subset-specific repertoire of ligands for E-selectin: whereas PSGL-1 and CD44 appear to contribute to binding activity in both myeloid and T lymphocytes ( 6,10,11 and the present study), the activity of CD43 appears to be restricted to T lymphocytes 5,7,45 and that of ESL-1 likely to neutrophils. 7,11 Moreover, our studies suggest that each of these ligands makes a specialized contribution to the different steps of leukocyte recruitment: both PSGL-1 and CD43 localize to the microvillus projections 46,47 and are therefore more suitable to mediate tethering and initial rolling interactions.…”
Section: Discussionsupporting
confidence: 50%
“…Early studies documented both positive and negative regulatory roles for CD43 in T cell activation (17)(18)(19), however these results may be reconciled by a recent report suggesting that CD43 plays a dynamic role in the progression of an immune response (12). Although earlier studies described a negative regulatory role for CD43 on T cell adhesion (18,20), more recent studies have demonstrated a positive role for CD43 in T cell homing to secondary lymphoid organs and peripheral tissues (21)(22)(23). For example, anti-CD43 mAbs have been shown to prevent the migration of T cells to pancreatic islets and thereby prevent the development of diabetes in a nonobese diabetic model (23).…”
mentioning
confidence: 46%
“…CD43 has been shown to play a role in the trafficking of T cells and monocytes to sites of inflammation (10,11). However, it is also purported to play an antiadhesive role in lymphocyte trafficking, suggesting increased trafficking of lymphocytes to some tissues in PFU LCMV-Armstrong i.c.…”
Section: Role For Cd43 In Trafficking Of Cd8 T Cells To Tissuesmentioning
confidence: 99%